Inhibiting vascular smooth muscle cell proliferation mediated by osteopontin via regulating gut microbial lipopolysaccharide: A novel mechanism for paeonol in atherosclerosis treatment - Shi, Xiaoyan; Wu, Hongfei; Liu, Yarong; Huang, Hanwen; Liu, Ling; Yang, Yulong; Jiang, Tingting; Zhou, Min; Dai, Min (Frontiers in Pharmacology, 2022)
Graphical Abstract